Pengaruh Faktor-Faktor Produksi Terhadap Keberhasilan Usaha Tani Kopi di Gunung Puntang Kecamatan Ciwidey Kabupaten Bandung Provinsi Jawa Barat - Nyi Yayat Ruwiyati; Euis Dasipah; Nendah Siti Permana (OrchidAgri, 2023)
Coffee is an important agricultural product that makes a major contribution to the Indonesian economy. In other words, as a source of farmers' income, job creation, foreign exchange earner, industrial product producer, and development. The problem with the upstream coffee farming industry is that the productivity level of Indonesian coffee is lower compared to other major coffee producing countries in the world. This study aims to determine the production factors that affect coffee production/harvest, the factors that affect the income of farmers and the factors that determine the increase in the feasibility of coffee cultivation on Mount Puntang. This research method uses descriptive analytic method with a qualitative approach. From the results of multiple regression analysis of the coffee production/yield of the Gunung Puntang farmers, the following equation is obtained, coffee production/yield. For the results of multiple linear regression analysis for the income of Gunung Puntang coffee farmers, it is obtained, where the variable number of trees (X2) and theta cost (X3) have an effect on coffee production/yields. For the feasibility of coffee farming, this farming business is feasible.